Smaller human populations are neither a necessary nor sufficient condition for biodiversity conservation. (January 2023) - Hughes, Alice C.; Tougeron, Kévin; Martin, Dominic A.; Menga, Filippo; Rosado, Bruno H.P.; Villasante, Sebastian; Madgulkar, Shweta; Gonçalves, Fernando; Geneletti, Davide; Diele-Viegas, Luisa Maria; Berger, Sebastian; Colla, Sheila R.; et al.
Abstract: Human population (often treated as overpopulation) has long been blamed as the main cause of biodiversity loss. Whilst this simplistic explanation may seem convenient, understanding the accuracy of the statement is crucial to develop effective priorities and targets to manage and reverse ongoing biodiversity loss. If untrue, the assertion may undermine practical and effective measures currently underway to counter biodiversity loss by distracting from true drivers, alienating some of the most diverse countries in the world, and failing to tackle the structural inequalities which may be behind global biodiversity declines. Through examining the drivers of biodiversity loss in highly biodiverse countries, we show that it is not population driving the loss of habitats, but rather the growth of commodities for export, particularly soybean and oil-palm, primarily for livestock feed or biofuel consumption in higher income economies. Thus, inequitable consumption drives global biodiversity loss, whilst population is used to scapegoat responsibility. Instead, the responsibilities are clear and have recently been summarized by the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services IPBES: Leverage points for biodiversity conservation lie in reducing unsustainable consumption through diet shifts, tracking supply chains, and technological innovation as well as ensuring sustainable production to reduce biodiversity losses associated with industrial agriculture. Highlights: Population is often mistakenly blamed as the main driver of biodiversity loss. However such arguments actually mis-apportion blame and hinder progress. Consumption patterns, largely from developed economies is a major driver of biodiversity loss. Maintaining global biodiversity will require reducing imported impacts. Sustainable supply chains and diets are crucial to counter current trends.